Analyzing the Company Merger Between Tokopedia and Gojek from the Perspective of Business Competition Law: Does it Lead to Anti-Competitive Behavior? - Sendari Waskita Putri; Kukuh Tejomurti (Fakultas Hukum Universitas Hang Tuah, 2021)
This study analyses how the merger between Tokopedia Ltd and AKAB Ltd is viewed from business competition law. The problem in this article is whether monopolistic actions and unfair business competition indicate the merger between these two largest digital companies? As normative legal research, the study uses an analysis of the statute approach and uses research sources for primary legal materials, secondary legal materials, and tertiary legal materials. The study results concluded that although they are a large company in the same market group, both are not indicated by monopolistic actions and unfair business competition. This is because the post-merger company does not control production/distribution/consumption in the community, and consumer behaviour is not centred on the post-merger company. When faced with the current development of the digital era, the relevant market theory is no longer relevant. Therefore, this study suggests that in addition to looking at the appropriate market conditions, merger assessments can also use consumer behaviour theory to determine whether a merger engages in monopolistic action and unfair business competition or not.